The legal deposit system as an element of the national culture (based on materials of the round table «The 5th anniversary of adoption of Novosibirsk region law “On legal deposit”») - N. I. Podkorytova; O. N. Alshevskya; N. M. Anfinogenova; S. A. Tarasova; D. M. Tsukerblat (Библиосфера, 2014)
Results of the discussion on the importance of the legal deposit system (LDS) for the library collections formation and book culture and evolution taken place at «round table» «The 5th anniversary of adoption of Novosibirsk region law “On legal deposit of documents”» are considered. A brief overview of 500-year history development of LDS is presented. The national system of legal deposit of published works appeared in 1783 in Russia. The Soviet legal deposit system, being finally formed in 1959, was one of the best in the world and included 398 sets of current editions. After the USSR collapse a negative attitude of printing environment to the legal deposit led to the fact that about 30% of published books were not included in the National Bibliography indices in 1991-1993. One of the modern trends on the regional publishing conservation and development, strengthen the local legal deposit system became fairs, shows, exhibitions, festivals, organized by library performing the functions of regional «book chambers»: so-called exhibitions of the legal deposit. The activity of Novosibirsk State Regional Scientific Library (NSRSL) and State Public Scientific-Technological Library of the Siberian Branch of the Russian Academy of Sciences (SPSTL SB RAS) on gathering legal deposit collections of the federal and federal subject level is examined; the dynamics of the regional legal deposit entering NSRSL in 1999-2013 is shown. The history analyses of LDS formation allowed the authors to draw conclusions on its influence on information, monuments and pieces of national culture preserving; forming the idea of copyright and intellectual property protection; on creating and developing such social institutions as the national bibliography and the national collections of publications forming. LDS is guaranteed and time-tested means of registration, preservation and analysis of the national information flow, a mirror of intellectual and spiritual life of each generation. Development of the information space, expansion of an electronic segment of the national information flow supposes modification of historical structures for the legal deposit collection and preservation, but requires an extremely thoughtful and cautious approach.